2018
DOI: 10.1097/qai.0000000000001597
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment Cascade in Children With Unsuppressed Viral Load—A Reality Check in Rural Lesotho, Southern Africa

Abstract: Only 1 of 5 children with unsuppressed initial VL under ART was retained in care and virally suppressed at 18 months of follow-up. ART programs must increase the focus onto the extremely vulnerable care cascade in children with unsuppressed VL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In children from the same cohort, virologic failure rates on bPI were lower than the previously reported 25.4% on a first-line regimen [7]. A pediatric study from a similar cohort in Lesotho reported failure rates (VL �80 copies/mL) of 28% on first-line treatment and, despite counseling, of 49% after switching to bPI [6]. This data indicates key challenges in the management of HIV-infected children such as ART-acceptance and -tolerability, inability to swallow the pills mainly designed for adults, and likely pharmacokinetic issues [20].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In children from the same cohort, virologic failure rates on bPI were lower than the previously reported 25.4% on a first-line regimen [7]. A pediatric study from a similar cohort in Lesotho reported failure rates (VL �80 copies/mL) of 28% on first-line treatment and, despite counseling, of 49% after switching to bPI [6]. This data indicates key challenges in the management of HIV-infected children such as ART-acceptance and -tolerability, inability to swallow the pills mainly designed for adults, and likely pharmacokinetic issues [20].…”
Section: Discussionmentioning
confidence: 60%
“…Additionally, in young children, a bPI-based treatment is currently started as a first-line therapy [3]. Children have a particularly high risk of virologic failure [6,7], which puts them in jeopardy of having a lack of effective treatment options in the future. Thus far, several studies from SSA found that poor adherence rather than viral resistance is the main driver of failure under bPI treatment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…2,8,10,12,14,[20][21][22][23][24][25][26][27][28] Clinical factors, nutritional status, duration on ART, ART regimen, WHO clinical stage, adherence, initial CD4 count, initial VL, count and EAC sessions completed have also been reported to have significant associations. [7][8][9][10]12,14,[20][21][22][23][24][27][28][29][30][31][32][33][34][35][36][37] Some important variables of potential association (ie, prophylaxis against opportunistic infections and nutritional status) with VL suppression were not considered in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have highlighted the practical challenges of applying this viral load algorithm. Key challenges include ensuring that patients with an elevated viral load receive enhanced adherence counselling and a follow‐up viral load, and those whose viral load remains elevated are switched to a new antiretroviral regimen . This has led to proposals to include HIV drug resistance testing as part of the algorithm, or to switch all patients following an initial elevated viral load .…”
Section: Introductionmentioning
confidence: 99%